DAMPAK BULLYING VERBAL BERBASIS MULTIKULTURAL TERHADAP SISWA DI SEKOLAH DASAR - Nur Afni Damayanti, Mahmud Yunus; Karina Trisna Putri, Alya Aprilia Putri Oskandar, Mila Gustina (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study examines the phenomenon of multicultural-based verbal bullying at SD Islam Izzuddin, an elementary school with cultural diversity and Islamic values. The aim is to analyze the forms, impacts, and handling strategies of verbal bullying in the school environment. The research employs a qualitative case study method, involving in-depth interviews with homeroom teachers and participatory observation to assess student social dynamics. Findings reveal that verbal bullying manifests as mockery related to regional accents, physical traits, or cultural identity, including racist remarks. The impacts include reduced self-confidence, social anxiety, and impaired learning concentration among victims. Teachers play a key role in fostering inclusivity through conflict mediation and restorative approaches, yet systematic strategies—such as integrating multicultural-religious education and peer support programs—are needed. The conclusion highlights the necessity of a holistic approach combining teacher roles, curriculum, and Islamic values to prevent verbal bullying in multicultural schools.